Propuesta de un manual de clasificación de puestos y un reglamento de admisión y empleo para la empresa constructora selva norte de la ciudad de Nueva Loja - Granda Cueva, Yoni Manuel (2015)
Build a Regulation of Admission and Employment and Classification Manual Positions Construction Company Forest North City Nueva Loja, permitting adequate human resource management, the main objective of the present study, for it was surveyed the manager and 83 employees currently working in the institution, and investigative methods and techniques that helped to gather relevant information to support the results achieved were used. Based on the information gathered from the techniques of applied research it became clear that the current chart does not show all charges exist in the company and it was found that the segregation of duties and responsibilities is not adequate, for that reason we proceeded to define the new organizational structure of the entity, defining five departments: operating, maintenance, human resources, general services and finance, which are reflected in the organizational, structural, positional and functional, 30 workstations distributed in the mentioned departments were defined, Manual classification of positions, which shows the roles, responsibilities and required for each job profile was developed. Furthermore, Regulation of Admission and employment in the different phases of the process was developed regulates noted. The proposal presented allow proper distribution of human talent available to the company, therefore the efficiency level will rise by raising the productivity and profitability of the construction, therefore their implementation and application is recommended.